(untitled) (American Journal of Islam and Society, 2008)
Brill’s new “Classics in Islam” series, a systematic reprinting of some of the seminal works in Islamic studies that have been out of print for decades, is a welcome initiative.As Dimitri Gutas, a former student, indicates in his introduction, Rosenthal’s achievement in this monograph is outstanding within an exceptionally productive and influential career. It is also somewhat unusual that a work first published over thirty years ago still remains unsurpassed, even if one may question some of the argument’s details and tendencies. Rosenthal often worked with manuscripts and unedited sources and, while we have the luxury of criticizing his judgments based on our access to superior critical editions, the contribution of the book remains singular. As befits a social and intellectual historian, Rosenthal’s survey commences with the philology of the word knowledge (`ilm) and works through instances in early Islam andArabic poetry before moving on to chapters on definition, theology, Sufism, philosophy, and finally concluding with a chapter on the social contexts and uses of knowledge. While there are now a number of works that deal with aspects of these chapters, no one has attempted to reconstruct a survey quite like this. Each chapter could well be the subject of monographs and, as Gutas suggests, numerous sections could act as inspiration for “untold dissertations.” Rosenthal begins with the claim that civilizations tend to revolve around meaningful concepts of an abstract nature that,more than anything else, give themtheir distinctive nature; in the case of Islam, this is the centrality of knowledge and the pursuit of knowledge. While he shifts from the plural to the singular and back, one retains the central point that the field of knowledge is unified. The fact is that Muslim scholars in very different fields of inquiry were able to retain a concept of `ilm that was broadly cognate and transferable ...